Espaces centrés et pouvoirs décentrés : l’exemple des fédérations villageoises dogon au XIXe siècle - Éric Jolly (Afriques)
In the 19th century, the southern part of the land of the Dogon stood out owing to its unusual political landscape, a mosaic of small village federations each of which grouped, in a territorial unit, a dozen or so localities unrelated by kinship. These original federations emerged out of a new relation to space during the second half of the 18th century as a result of increasing warfare and raiding in the context of a denser, more diversified local population. Given mounting military pressure from neighboring states, resident groups no longer sought to appropriate a territory but to defend it by establishing its unity in the center, at the presumed place of foundation. As a political and religious crossroads, this center was not only a public meeting place expressing unity but also the axis of an egalitarian distribution of power between all villages located in the same territory.